Apple pomaces derived from mono-varietal Asturian ciders production are potential source of pectins with appealing functional properties. (15th July 2021) - Calvete-Torre, Inés; Muñoz-Almagro, Nerea; Pacheco, M. Teresa; Antón, María José; Dapena, Enrique; Ruiz, Lorena; Margolles, Abelardo; Villamiel, Mar; Moreno, F. Javier
Graphical abstract: Highlights: Nine mono-varietal industrial apple pomaces from cider production are characterized. Apple pomaces are rich in essential minerals, polyphenols and fibers (i.e., pectin). Ultrasound-assisted extraction produces high-purity pectin. Pectin from Sol variety may have good gelling properties based on GalA levels. Pectin from Per/Reg varieties may act as biofunctional ingredients (GalA/Rha ratio). Abstract: Comprehensive chemical characterization of nine mono-varietal apple pomaces obtained from the production of ciders with PDO is described. They were rich in essential minerals, fibers (35–52.9 %), and polyphenols. High levels in GalA (11.8–21.6 %), revealed the suitability of these apple pomaces as efficient sources of pectins. Extracted pectins showed high variability in monomer composition, with degrees of methylesterification, strongly associated with pectins functional properties, ranging from 58 to 88 %. For a subset of apple pomace varieties, pectin extraction was accomplished by conventional acid heat treatment or ultrasound. Despite ultrasound-assisted extraction did not improve pectin yield, it minimized levels of "non-pectin" components as revealed by the low content of Glc/Man, leading to the obtainment of high-purity pectin. Our work highlights the key role played by the selection of the apple variety to streamline the potential food applications (gelling/thickening agents or prebiotics) of the extracted pectins that largely depend on their structural features.